Consolidarea dimensiunii geopolitice a rezilienței securității naționale a Republicii Moldova - Ungureanu, Veaceslav (Editura USM, 2024)
Currently, in the context of the war between the Russian Federation and Ukraine, which generates the amplification of the risks and threats to regional security, while also jeopardizing the national security of the Republic of Moldova, determines the need to organize national debates at the levels of academia, civil society and the political class on strengthening the geopolitical dimension of the resilience of the national security of the Republic of Moldova, by capitalizing on the opportunities offered as a result of deepening the political-military relations with the North-Atlantic Alliance in order to strengthen the national security system, but also by the possibility of changing the geopolitical status of permanent neutrality of the Republic of Moldova to join the North-Atlantic Alliance. At the same time, the hesitation of the Republic of Moldova to realize the geopolitical alternative of ensuring the national security of the Republic of Moldova would determine the preservation of the geopolitical status of permanent neutrality, which does not ensure, but only increases the vulnerability degree of the national security, as well as keeping the geopolitical position of a buffer state between two poles of power, which will maintain it in the sphere of geopolitical influence of the Russian Federation, thus diminishing its geopolitical potential to ensure national security.
Strengthening the geopolitical dimension of the resilience of the national security of the Republic of Moldova
Keywords: geopolitical dimension; national security; permanent neutrality; buffer state; geopolitical interests; North Atlantic Alliance